Jingmenviruses: Ubiquitous, understudied, segmented flavi-like viruses - Colmant, Agathe M. G.; Charrel, Rémi N.; Coutard, Bruno (Frontiers in Microbiology, 2022)
Jingmenviruses are a group of flaviviruses identified recently, in 2014. These flaviviruses are unique due to the segmented nature of their genome. The prototype jingmenvirus, Jingmen tick virus (JMTV), was discovered in Rhipicephalus microplus ticks collected from China in 2010. Jingmenviruses genomes are composed of four to five segments, encoding for up to seven structural proteins and two non-structural proteins, both of which display strong similarities with other flaviviral non-structural proteins (NS2B/NS3 and NS5). Jingmenviruses are currently separated in two phylogenetic clades. One clade includes tick- and vertebrate-associated jingmenviruses, which have been detected in ticks and mosquitoes, as well as in humans, cattle, monkeys, bats, rodents, sheep and tortoises. In addition to these molecular and serological detections, over a hundred human patients tested positive for jingmenviruses after developing febrile illness and flu-like symptoms in China and Serbia. The second phylogenetic clade includes insect-associated jingmenvirus sequences, which have been detected in a wide range of insect species, as well as in crustaceans, plants and fungi. In addition to being found in various types of hosts, jingmenviruses are endemic, as they have been detected in a wide range of environments, all over the world. Taken together, all of these elements show that jingmenviruses correspond exactly to the definition of emerging viruses at risk of causing a pandemic, since they are already endemic, have a close association with arthropods, are found in animals in close contact with humans and have caused sporadic cases of febrile illness in multiple patients. Despite these arguments, the vast majority of published data is from metagenomics studies and many aspects of jingmenvirus replication remain to be elucidated, such as their tropism, cycle of transmission, structure, mechanisms of replication and restriction or epidemiology. It is therefore crucial to prioritize jingmenvirus research in the years to come, to be prepared for their emergence as human or veterinary pathogens.